Governing for Excellence in the Social Care Sector - The Role of Self-Governance in Ireland's Evolving Social Care Profession - McTaggart, Breda; Barrins, Sinead; McCarthy, John (International Journal of Practice-based Learning in Health and Social Care, 2017)
Social care work in Ireland remains a poorly understood profession, despite its growing importance within the wider health and welfare sectors. Higher Educational programmes, especially practice-based aspects, in conjunction with the imminent professional registration of social care graduates, will help with identity formation and solidification of this role (McGregor 2011). However, this professional registration has yet to occur and, on its own, will not guarantee the delivery of a quality service to the user. Using less commonly used professional development concepts of self-governance, self-regulation, impression management and identity capital, this article will explore how social care professional identity may be nurtured, developed and supported within professional practice learning and social care worker environments and, in so doing, support a quality service delivery within the social care space.